2015
DOI: 10.1007/s10517-015-3089-0
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Glutathione Antioxidant System and NADPH-Generating Enzymes in Rats with Experimental Rheumatoid Arthritis

Abstract: Induction of rheumatoid arthritis in rats was accompanied by an increase in diene conjugate content and glutathione reductase and glutathione peroxidase activities in muscles and blood serum. These changes can be related to mobilization of the glutathione reductase/glutathione peroxidase system coupled with intensification of free radical oxidation. In addition, activity of glucose-6-phosphodehydrogenase and NADP-dependent isocitrate dehydrogenase increased, which can be related to increased demand of NADPH fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…On the 15th day after the resulting inflammation in the absence of treatment, the specific activity of all antioxidant defense enzymes (SOD, catalase, GR, G6PD, LDR directed and LDR reversed) increased, which characterizes their activation as a response to oxidative stress developing against the background of RA. These results are consistent with the studies of the authors, which demonstrated a significant increase in enzyme activity in various tissues (liver, heart, muscles, blood serum), from 1.2 to 1.7 times [48][49][50][51][52].…”
Section: Biological Activity Of the Fa Patch On The Adjuvant-induced ...supporting
confidence: 93%
“…On the 15th day after the resulting inflammation in the absence of treatment, the specific activity of all antioxidant defense enzymes (SOD, catalase, GR, G6PD, LDR directed and LDR reversed) increased, which characterizes their activation as a response to oxidative stress developing against the background of RA. These results are consistent with the studies of the authors, which demonstrated a significant increase in enzyme activity in various tissues (liver, heart, muscles, blood serum), from 1.2 to 1.7 times [48][49][50][51][52].…”
Section: Biological Activity Of the Fa Patch On The Adjuvant-induced ...supporting
confidence: 93%
“…Apocynin is a well-known NADPH-oxidase inhibitor, and there have been several studies on the therapeutic effect of apocynin in chronic inflammatory diseases such as atherosclerosis [7], rheumatoid arthritis [10], airway inflammation [9], stroke and IBD [12,13]. Many in vitro and in vivo experiments have shown the therapeutic potential of apocynin as an anti-inflammatory agent.…”
Section: Discussionmentioning
confidence: 99%
“…The activity of the antioxidant enzymes, such as superoxide dismutase (SOD), catalase, glutathione peroxidase (GP), and glutathione reductase (GR), was evaluated in hemolyzed erythrocytes. The content of SOD was determined by calculating the speed of auto-oxidation of quercetin in the presence of tetramethylethylenediamine [ 40 ]; the activity of catalase was measured by the reaction with ammonium molybdate [ 41 ]; the activity of GP was deduced from the reaction between sulfhydryl groups of reduced glutathione and Elman's reagent [ 42 ]; and the GR-activity was assessed by the NADPH-dependent conversion of oxidized glutathione to its reduced form [ 43 ]. The total protein content was determined by the Bradford microassay [ 44 ].…”
Section: Methodsmentioning
confidence: 99%